Fourth grade rats - Spinelli, Jerry; Casale, Paul (New York, NY : Scholastic, Inc., 1991)
Suds learns that his best friend is wrong. You don't have to be a tough guy, a "rat," to be a grown up fourth grader.
Accelerated Reader AR
Keywords: Friendship -- Fiction; Conduct of life -- Fiction; Schools -- Fiction